(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Background of the study: The Paliyars tribes are socially backward people with different culture and the present study conducted among the ST adolescent girls in Kodaikanal region to find out the nutritional status of them. Adolescent girls are more vulnerable to nutritional deficiencies especially anemia and under nutrition. The socio demographic characteristics essential to determine the health status of adolescent girls especially tribal adolescent girls. Objectives: To study the socio demographic characteristics of scheduled tribe adolescent girls in Kodaikanal. Methodology: The structured questionnaire was used to collect the socio demographic factors Results and Conclusion: The results concluded that, majority of the 38% of girls belonged to high income (above Rs.14500/month) and only 16% of the adolescent girls belonged to a low-income group (Rs.3300/month). About 41% belonged to the extended nuclear family and 25% were from nuclear family system. The higher percent (51%) were from medium-sized family (5-7 members) and 19% were from the small family (2-4 members) system.